Implementasi Program Kampung KB dalam Meningkatkan Kesejahteraan Masyarakat Melalui UPPKS (Usaha Peningkatan Pendapatan Keluarga Sejahtera) di Desa Lerep Kecamatan Ungaran Barat - Alhukam, Nabilla Arsya; Susanti, Martien Herna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the Quality Family Village (Kampung KB) program through the Prosperous Family Income Enhancement Effort (UPPKS) in Lerep Village, as well as to identify obstacles in its execution. A qualitative approach was employed, utilizing data collection techniques such as interviews, observation, and document analysis. Research informants included program implementers and community members involved in UPPKS activities, while data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing and verification. The results indicate that the program has been implemented effectively, contributing to community economic empowerment through the development of local potential-based enterprises. Program success was facilitated by effective communication, resource availability, the commitment of both implementers and the community, and a clear division of tasks, all of which helped enhance business skills and independence. However, challenges remain, including limited capital and production facilities, suboptimal marketing, and uneven community participation. Improvement efforts have been pursued through training, mentoring, digital promotion, MSME exhibitions, and cross-sector collaboration. These findings underscore that the program's success depends not only on the execution of activities but also on resource support, coordination, and sustained mentoring.